O Ernesto Nazareth de Sérgio Assad: um estudo de procedimentos de reelaboração ao violão - Paula, Daniel Pires de (2021)
This work aims to unveil Sérgio Assad's technical and musical procedures present in his classical guitar transcriptions, based on the works by Ernesto Nazareth that make up the musical score album The music of Ernesto Nazareth. Such research was carried out by comparative analysis of scores, as well as recordings of the works, resources that allowed us to identify and systematize the procedures, supported by the theoretical foundations of Flávia Pereira about musical re-elaboration and concepts related to the classical guitar idiomatism by Fábio Scarduelli and Sérgio Ribeiro. In the course of our proposal, we noticed a considerable freedom towards Nazareth's writing, but which final result preserves similar effects to the original ones, or even new effects, giving new meaning to the relations of contrasts between sections in some of the works. After a contextualization of musical re-elaboration, the reader will find an overview of the categories of procedures pervading the entire album, as well as specific analyzes of three representative works, which also illustrate how Assad uses his solutions.